Lean Construction: Enhancing Efficiency And Quality In The Construction Industry - Mhod Razif Idris; Andri Hermawan (Ann Publisher, 2025)
Background. Lean Management and Lean Construction have been widely recognized as effective approaches to improving efficiency, reducing waste, and enhancing organizational performance. However, the readiness of construction organizations—particularly State-Owned Enterprises (SOEs)—to implement Lean Management remains insufficiently explored, especially in developing countries. Aims. This study aims to assess the factors influencing Lean Management implementation and to evaluate the readiness level of Indonesian construction SOEs using a quantitative approach. The research adopts Lean Management as its theoretical foundation and applies the Lean Construction Maturity Model (LCMM) as the primary measurement framework to capture organizational readiness comprehensively. Methods. Data were collected through a structured questionnaire distributed to management-level respondents across six Indonesian state-owned construction companies, involving division heads, section managers, staff, and project managers, with a total sample of approximately 250 respondents. The analysis employs linear regression within a structural model to examine the relationships among key readiness factors, including leadership, culture and behavior, competence, continuous improvement support, processes and tools, organizational change, work environment, business results, and learning and competency development. Result. The findings are expected to provide empirical insights into the interdependencies among these factors and to identify critical readiness gaps that may hinder effective Lean Management implementation. Conclusion. This study contributes theoretically by extending the application of LCMM to Lean Management readiness assessment and practically by offering a structured diagnostic framework for SOEs seeking to enhance Lean adoption in the construction sector.